Pengaruh Keterampilan Karyawan Dan Pengalaman Kerja Dalam Meningkatkan Kinerja Karyawan di PT. So Good Food Kota Medan - Aminuddin Aminuddin; Irvan Rolyesh Situmorang (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
This study aims to determine how much influence the Employee Skills, Work Experience in Improving Employee Performance at PT. So Good Food Medan City. The research methodology used is a quantitative descriptive method. The population in this study are employees from PT. So Good Food Medan City as many as 37 employees. Population and sample in research at PT. So Good Food Medan has 37 employees. The sampling technique uses a saturated sample. The data sources in this study are primary data, namely data obtained directly from the research location and secondary data, namely books and journals related to it. Data collection techniques are observation, interviews, and questionnaires. The data analysis technique used is multiple linear regression analysis. The results of multiple regression analysis are Y = 0.596 + 0.602X1 + 1.046X2 + e which shows skills and work experience have a positive and significant effect on employee performance. The results of the partial test (t) show that skills have a positive and significant effect on employee performance where it can be seen that the tcount value is 3.862 ttable 1.690 and the work experience variable also has a positive and significant effect on employee performance where it can be seen that the tcount value is 5.929 ttable 1.690. The significance value of F is less than 5% or 0.05 or the value of Fcount = 92.762 Ftable 3.28. The result of the coefficient of determination is 0.845, this shows that 84.5% of employee performance variables are influenced by skills and work experience, in other words, skills and work experience affect employee performance by 84.5%, while the remaining 15.5% are influenced by other factors outside of this study